Altered gene expression of VEGF, IGFs and H19 lncRNA and epigenetic profile of H19-DMR region in endometrial tissues of women with endometriosis - Sedigheh Kamrani; Elham Amirchaghmaghi; Firouzeh Ghaffari; Maryam Shahhoseini; Kamran Ghaedi (BMC, 2022)
Abstract Background Endometriosis, as chronic estrogen-dependent disease, is defined by the presence of endometrial-like tissue outside the uterus. Proliferation of endometrial tissue and neoangiogenesis are critical factors in development of endometriosis. Hence, vascular endothelial growth factor (VEGF) as well as insulin‐like growth factor 1 and 2 (IGF1, 2) may be involved as inducers of cellular proliferation or neoangiogenesis. Imprinted long noncoding RNA H19 (lncRNA H19) has been suggested to be involved in pathogenesis of endometriosis via regulation of cellular proliferation and differentiation. Epigenetic aberrations appear to play an important role in its pathogenesis. The present study was designed to elucidate VEGF, IGF1, IGF2 and H19 lncRNA genes expression and epigenetic alterations of differentially methylated region (DMR) of H19 (H19-DMR) regulatory region in endometrial tissues of patients with endometriosis, in comparison with control women. Methods In this case-control study, 24 women with and without endometriosis were studied for the relative expression of VEGF, IGF1, IGF2 and H19 lncRNA genes using real-time polymerase chain reaction (PCR) technique. Occupancy of the MeCP2 on DMR region of H19 gene was assessed using chromatin immunoprecipitation (ChIP), followed by real-time PCR. Results Genes expression profile of H19, IGF1 and IGF2 was decreased in eutopic and ectopic endometrial tissues of endometriosis group, compared to the control tissues. Decreased expression of H19 in ectopic samples was significant in comparison with the controls (P < 0.05). Gene expression of VEGF was increased in eutopic tissues of endometriosis group, compared to control group. Whereas its expression level was lower in ectopic lesions versus eutopic and control endometrial samples. ChIP analysis revealed significant and nearly significant hypomethylation of H19-DMR region II in eutopic and ectopic samples, compared to the control group respectively. This epigenetic change was aligned with expression of IGF2. While methylation of H19-DMR region I was not significantly different between the eutopic, ectopic and control endometrial samples. Conclusion These data showed that VEGF, IGF1, IGF2 and H19 lncRNA genes expression and epigenetic alterations of H19 lncRNA have dynamic role in the pathogenesis of endometriosis, specifically in the way that hypomethylation of H19-DMR region II can be involved in IGF2 dysregulation in endometriosis.